Australian perspectives on global air and space power past, present, future - Townsend, Nicole; Pandey, Kus; Pendlebury, Jarrod (Routledge, Taylor & Francis Group, 2023)
"This book surveys historical and emerging global air and space power issues and provides a multidisciplinary understanding of the application of air and space power in the past and present, as well as exploring potential future challenges that global air forces may face. Bringing together leading and emerging academics, professionals, and military personnel from Australia within the field of air and space power, this edited collection traces the evolution of technological innovations, as well as the ethical and cultural frameworks which have informed the development of air and space power in the 20th and 21st centuries, and contemplates its future. It covers topics such as the insurgent use of drones, the ethics of air strikes, the privatisation of air power, the historical trajectory of air power strategy, and the sociological implications of an 'air force' identity. While many of the chapters use Australian-based case studies for their analysis, they have broader applicability to a global readership, and several chapters examine other nations' experiences, including those of the United States, and the United Kingdom. This accessible, illuminating book is an important addition to contemporary air and space power literature, and will be of great interest to students and scholars of air power, air warfare, military and international history, defense studies, and contemporary strategic studies, as well as military professionals."